Classification of Causes and Strategies for Curbing Market Fire in Nigeria - Nnamdi ILodiuba; Ify L. Nwaogazie; John Ugbebor (Archives of Current Research International, 2017)
Classification of causes of market fire in Nigeria is a study aimed at identifying and classifying the causes of market fire in Nigeria from the market users’ perspective. The study considered markets with high commercial activities and they were selected from three major cities, namely Lagos, Port Harcourt and Onitsha. Sixty questions on the causes of market fire were designed and distributed to 1074 shop owner/traders (respondents). The factor analysis method was adopted to streamline the questions into six categories and they were ranked. Results showed that the most common cause of market fire in Nigerian is “general storing” and this category attained a commonality ratio of 0.09284. Other causes of fire in markets included electrical installation which ranked second with a commonality ratio of 0.08071. The third to the sixth in that order are, disposal and knowledge of market locations, market exit points, regulations regarding markets and awareness and fire emergency plan. A design plan for an ideal market is provided taking cognizance of the following: ventilation, fire wall and roofs, building in clusters, electrical wiring in conduits, firefighting tools in place, general storage facilities, and dedicated parking area and that for smoking, etc. It is recommended that Government should institute fire professionals to handle design and operation of markets.